(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and objective: Pinctada Maxima which is one of the nacres some of the structures of marine biota whose contents can be used to build tooth structures are damaged due to disease. The aim of this study is to see the effectiveness of pearl shells on osteogenesis of bone graft in periodontal tissue and to determine the effectiveness of pearl shells on periodontal tissue through the formation of osteoblasts so that later it can be considered as an ideal alternative bone graft. Methods: Cavia Porcellus were divided into 3 groups of 30: Bone graft using Hydroxyapatite Pinctada maxima, Bovine Xenograft as positive control and placebo as negative control, then sacrificed on 14th and 21st days. The Real Time-Polymerase Chain Reaction (RT-PCR) analysis was performed to see the expression of osteocalcin (OCN) and Scan electron microscope (SEM) examination to see the formation of osteoblasts Results: Data were analyzed with Independent T test and processed in SPSS 24.0. It was shown that the osteoblast increases in the Batan and Placebo groups from day 14 to day 21, in contrast to the Hydroxyapatite Pinctada Maxima test group with SEM analysis. For the OCN increase in all the Batan, Placebo and Hydroxyapatite Pinctada Maxima groups and the most significant increase was in the Hydroxyapatite Pinctada Maxima Test group although it was not significant with the RT-PCR analysis. Coclusion: Hidroxyapatite pinctada maxima has quite good potential as a bone graft.